Mama the alien - Colato Lainez, Rene; Lacamara, Laura (New York : Children's Book Press, an imprint of Lee & Low Books Inc., 2016)
"A young girl misunderstands the word alien on her mother's Resident Alien Card and let's her imagination run wild, coming to the conclusion that her mother is from outer space. Includes author's note and glossary"--
Keywords: Immigrants -- Fiction; Citizenship -- Fiction; Hispanic Americans -- Fiction; Spanish language materials -- Bilingual